Identification and Characterization of the ERF Subfamily B3 Group Revealed GhERF13.12 Improves Salt Tolerance in Upland Cotton - Lu, Lili; Qanmber, Ghulam; Li, Jie; Pu, Mengli; Chen, Guoquan; Li, Shengdong; Liu, Le; Qin, Wenqiang; Ma, Shuya; Wang, Ye; Chen, Quanjia; Liu, Zhao (Frontiers in Plant Science, 2021)
APETALA2 (AP2)/ethylene response factor plays vital functions in response to environmental stimulus. The ERF subfamily B3 group belongs to the AP2/ERF superfamily and contains a single AP2/ERF domain. Phylogenetic analysis of the ERF subfamily B3 group genes from Arabidopsis, Gossypium arboreum, G. hirsutum, and G. raimondii made it possible to divide them into three groups and confirmed that the ERF subfamily B3 group genes are conserved in cotton. Collinearity analysis identified 172 orthologous/paralogous gene pairs between G. arboreum and G. hirsutum, 178 between G. hirsutum and G. raimondii, and 1392 in G. hirsutum. The GhERF subfamily B3 group gene family experienced massive gene family expansion through either segmental or whole genome duplication events, with most genes showing signature compatible with the action of purifying selection during evolution. Most G. hirsutum ERF subfamily B3 group genes are responsive to salt stress. GhERF13.12 transgenic Arabidopsis showed enhanced salt stress tolerance and exhibited regulation of related physiological indices and enhanced expression of genes participating in ABA signaling, proline biosynthesis and ROS scavenging. In addition, the silencing of the GhERF13.12 gene reduced salt stress in cotton. These results indicate that the ERF subfamily B3 group had remained conserved during evolution and that GhERF13.12 induces salt stress tolerance in Arabidopsis and cotton.